2023
DOI: 10.1007/s10753-023-01849-8
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol Attenuates Gouty Arthritis by Regulating the Balance of Th17/Treg Cells and Secretion of IL-17

Abstract: BackgroundKaempferol is a common avonoid aglycone widely found in plants. It exhibits bene cial therapeutic effects in the treatment of arthritis. However, the effects of kaempferol on gouty arthritis (GA) have not been veri ed. This study aimed to explore the potential mechanisms by which kaempferol regulates GA by network pharmacology and experimental validation. MethodsPotential drug targets for GA were identi ed with a protein-protein interaction network. Then, we performed a KEGG pathway analysis to eluci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The outcomes revealed that the five main active ingredients displayed a strong binding potential to CXCL8, IL-1β, IL-6, MMP9, and PPARG. Li's experiments illustrated that kaempferol could mitigate mechanical abnormal pain, ankle edema, and inflammation in MSU by inhibiting the expression of IL-1β, IL-6, TNF-α, and TGF-β1 while restoring Th17/Treg imbalance [ 52 ]. Furthermore, kaempferol demonstrates anti-inflammatory properties by increasing the expression levels of CXCL8 and PPARG and inhibiting NF-kB activation [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The outcomes revealed that the five main active ingredients displayed a strong binding potential to CXCL8, IL-1β, IL-6, MMP9, and PPARG. Li's experiments illustrated that kaempferol could mitigate mechanical abnormal pain, ankle edema, and inflammation in MSU by inhibiting the expression of IL-1β, IL-6, TNF-α, and TGF-β1 while restoring Th17/Treg imbalance [ 52 ]. Furthermore, kaempferol demonstrates anti-inflammatory properties by increasing the expression levels of CXCL8 and PPARG and inhibiting NF-kB activation [ 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research has indicated a significant correlation between MMP9 and the IL-17 signaling pathway. By enhancing IL-17 signaling pathway transduction, drugs can potentially exhibit anti-inflammatory effects by upregulating the downstream target MMP9 [ 52 , 71 ]. PPARG, a nuclear hormone receptor, is found in many tissue cells and is important for controlling adipose tissue differentiation, metabolism, and protecting bones and joints.…”
Section: Discussionmentioning
confidence: 99%
“…The results of enrichment analysis showed that these targets are mainly involved in inflammation-related signaling pathways. Many of the active ingredients of Zhenqi Granule, including quercetin, kaempferol, (3R)-3-(2-hydroxy-3,4-dimethoxyphenyl)chroman-7-ol, luteolin, 7-O-methylisomucronulatol, formononetin, isorhamnetin, beta-sitosterol, hederagenin, and 3,9-di-O-methylnissolin, have been reported to have anti-inflammatory effects [ 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. The basic principle of DSS-induced acute colitis in mice is that DSS destroys the intestinal epithelium [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 43 ] Kaempferol and Luteolin can suppress the pro-inflammatory cytokine expression, such as TNFα, IL-6, and IL-1. [ 44 , 45 ] Additionally, quercetin increases the angiogenic factor VEGFA, which drives endothelial cell proliferation, migration, and vascular tissue regeneration. Diosgenin can upregulates VEGFA and promotes angiogenesis via estrogen receptor (ER)-related PI3K/Akt and p38 mitogen-activated protein kinase (MAPK) pathways in preosteoblast-like cells.…”
Section: Discussionmentioning
confidence: 99%